Effectiveness of neutrophil-to-lymphocyte and platelet-to-lymphocyte ratios in predicting the incidence of nausea and vomiting after total knee arthroplasty in patients with hemophilia A - Feng, Denghe; Wang, Dong; Gu, Changping; Lv, Meng; Liu, Zaibo; Wang, Yuelan (Frontiers in Surgery, 2023)
Objective To investigate the ability of preoperative neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) to predict postoperative nausea and vomiting (PONV) after total knee arthroplasty (TKA). Methods The clinical data of 108 male patients with hemophilia A who underwent TKA an our institution were collected and analyzed. Confounding factors were adjusted by propensity score matching. The best cutoffs of the NLR and PLR were determined by the area under the receiver operating characteristic curve (ROC). The predictive ability of these indexes was assessed by measuring the sensitivity, specificity, and positive and negative likelihood ratios. Results There were significant differences in the use of antiemetics (p = 0.036) and the incidence of nausea (p < 0.001) and vomiting (p = 0.006) between the two groups (NLR <2 and ≥2). An increase in preoperative NLR was an independent risk factor for PONV in patients with hemophilia A (p < 0.05). ROC analysis showed that NLR significantly predicted the occurrence of PONV (cutoff value: 2.20, ROC: 0.711, p < 0.001). In turn, the PLR did not strongly predict PONV. Conclusions The NLR is an independent risk factor for PONV in patients with hemophilia A and can significantly predict this event. Thus, follow-up monitoring is essential for these patients.